Effects of Health Education on Knowledge and Preventive Behaviors Related to ARI and Pneumonia in Timor-Leste - Yarwin Yari; Hardin La Ramba; Daud Wiberdjohn Tafuli; Nia Rosliany; Rizqa Wahdini; Ribka Sabarina Panjaitan; Khalida Ziah Sibualamu; Wagida Ahmed Nasor Abdelrahim (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Respiratory tract infections, particularly Acute Respiratory Infections (ARI) and pneumonia, remain important public health concerns in rural communities with limited access to health information.Aims: This community-based health education program aimed to assess changes in community knowledge and preventive behaviors related to ARI and pneumonia among adults in Vatuboro Village, Liquica District, Timor-Leste.Methods: A pre-experimental one-group pretest–posttest design was used involving 20 participants selected through purposive sampling. The intervention consisted of interactive health education sessions, including lectures, group discussions, and demonstrations on respiratory disease prevention practices. Data were collected using structured questionnaires and analyzed using descriptive statistics and paired t-tests with a significance level of p < 0.05.Conclusion: Continuous and contextually appropriate health education programs are recommended to support community health literacy and respiratory disease prevention.